EVALUATION OF GLYCEMIC CONTROL IN PATIENTS WITH TYPE 2 DIABETES MELLITUS WITH AND WITHOUT MICROVASCULAR COMPLICATIONS - MUKESH G. GOHEL (International Journal of Pharma and Bio Sciences, 2013)
Diabetes mellitus (DM) includes a group of metabolic disorders that share common phenotype of hyperglycemia. Assessing glycemia in diabetes has always been a challenge. Aim of this study is to evaluate glycemic control in patients with type 2 DM patients with and without microvascular complications. HbA1c, FBS and PP2BS were estimated as measure of glycemic control. A cross sectional study consists of 150 subjects: 50 patients having type 2 DM without any microvascular complications (Group II), 50 patients with type 2 DM with one or more microvascular complications (Group III) and 50 normal healthy control (Group I) were selected. Study shows increased value of HbA1c, FBS and PP2BS level in group II and group III patients compared to group 1 (higher than upper reference value in group III). These finding indicate that poor glycemic control plays important role in the pathophysiology and management of type 2 DM and its complications.